The complex puzzle underlying the pathophysiology of acute coronary syndromes: from molecular basis to clinical manifestations. (December 2012) - Cimmino, Giovanni; Conte, Stefano; Morello, Alberto; D'Elia, Saverio; Marchese, Valeria; Golino, Paolo
Acute coronary syndromes (ACS) still represent a major cause of death in Western countries; in the vast majority of cases, coronary atherosclerosis represents the common pathological lesion to all forms of ACS. It is currently believed that plaque complication (rupture, fissuration, and so on), with the consequent superimposed thrombosis, is a key factor ultimately leading to the clinical occurrence of ACS. Over the last two decades, our understanding of the basic mechanisms involved in the pathophysiology of ACS has progressed significantly and the crucial role of inflammation in this phenomenon is now widely recognized. The sequence of events is represented by plaque complication (i.e., rupture, fissuration or erosion), exposure of tissue factor and other prothrombotic substances, such as von Willebrand factor and collagen, to the blood flow, activation of platelets and of the coagulation cascade and thrombus formation within the coronary artery. However, not all complicated plaques cause the clinical occurrence of ACS and similar complicated plaques may cause different clinical manifestations. A complex interaction between different factors, such as arterial vessel wall substrates, degree of inflammation of the culprit lesion, local rheological characteristics of blood flow, as well as factors present in the circulating blood, will determine the severity (complete vs incomplete occlusion) and the persistence of coronary blood flow cessation, which, in turn, will be largely responsible for the clinical picture. Targeting tissue factor, the key player in the activation of the coagulation cascade, may represent an important therapeutic strategy to prevent the clinical manifestation of ACS.